Self-Assembled Heterostructures Selective Growth of Metallic Nanoparticles on V2 -VI3 Nanoplates - Dun, Chaochao (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.